2012
DOI: 10.1123/ijsnem.22.3.225
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Dietary Strategy to Make Weight While Improving Mood, Decreasing Body Fat, and Not Dehydrating: A Case Study of a Professional Jockey

Abstract: Professional jockeys are unique among weight-making athletes, as they are often required to make weight daily and, in many cases, all year-round. Common methods employed by jockeys include dehydration, severe calorie restriction, and sporadic eating, all of which have adverse health effects. In contrast, this article outlines a structured diet and exercise plan, employed by a 22-yr-old professional National Hunt jockey in an attempt to reduce weight from 70.3 to 62.6 kg, that does not rely on any of the aforem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 18 publications
3
33
1
Order By: Relevance
“…In a recent case-study on a professional Jump jockey, body mass was reduced by 8 kg over a 9-week period using 3 g.kg − 1 bw of CHO, without any intentional dehydration [ 37 ] despite the jockey reporting increased energy and vigour supporting our suggestion that 3 g.kg − 1 bw of CHO is appropriate for jockeys.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…In a recent case-study on a professional Jump jockey, body mass was reduced by 8 kg over a 9-week period using 3 g.kg − 1 bw of CHO, without any intentional dehydration [ 37 ] despite the jockey reporting increased energy and vigour supporting our suggestion that 3 g.kg − 1 bw of CHO is appropriate for jockeys.…”
supporting
confidence: 74%
“…The mean CHO intakes of both Flat and Jump jockeys are lower than previously reported in Irish [ 9 ] and NZ jockeys [ 20 ] which fall considerably short of the suggested mid-range CHO intake of 6 g.kg − 1 bw recommended for athletes [ 28 ] . Previous studies on jockeys have suggested that such a low CHO intake may be insuffi cient [ 9 , 20 ] however, due to the need to ride at the required weight, combined with the apparent low energy demands of a typical race observed by our group, albeit in simulated race-riding [ 37 ] , and contrary to the view that riding has a high energy expenditure [ 34 ] we believe that such values are appropriate for jockeys. If jockeys were to consume 6 g.kg − 1 bw per day of CHO, along with a conservative protein intake of 1.2 g.kg − 1 bw and a fat intake of 1 g.kg − 1 bw this would result in a mean daily energy intake of 8.87 MJ and 10.33 MJ per day for Flat and Jump jockeys, respectively.…”
contrasting
confidence: 60%
See 1 more Smart Citation
“…Our data are in agreement with previous studies [13,21,36], and show that dietary restriction induces alterations in psychological parameters. However, there is a lack of consensus in the literature about this topic [19,59]; these discrepancies are linked to the dietary strategy used to make weight [58]. Recently, Helms et al [24] showed that a highprotein/low-fat diet during short-term weight loss may be more effective at mitigating mood disturbance, fatigue, diet dissatisfaction and stress than a moderate-protein/moderate-fat diet in resistance-trained males.…”
Section: Discussion ▼mentioning
confidence: 99%
“…weight loss alters perceived exertion and mood by increasing tension, anger, fatigue, and confusion and decreasing vigour [11,15,21,28,36]. These alterations depend on dietary strategy to make weight [58]; this temporarily reduced mental state could be an outcome of the various physiological effects induced by weight regulation, such as dehydration and hypoglycaemia [42,44]. Nevertheless, the effects of energy restriction on mood are still in debate [19,59].…”
mentioning
confidence: 99%